2017
DOI: 10.1007/s11910-017-0787-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Alzheimer’s Disease: the Importance of Polygenic and Epistatic Components

Abstract: Purpose of Review We aimed to summarize the recent advances in genetic findings of Alzheimer’s disease (AD), focusing on traditional single-marker and gene approaches and non-traditional ones, i.e., polygenic and epistatic components. Recent Findings Genetic studies have progressed over the last few decades from linkage to genome-wide association studies (GWAS), and most recently studies utilizing high-throughput sequencing. So far, GWASs have identified several common variants characterized by small effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 91 publications
0
35
0
Order By: Relevance
“…The only other oligogenic influence was that of the well‐known APOE4 / TOMM40 variants. There was nominal association with Alzheimer's pathological diagnosis in this report, though PTPRD has not previously displayed robust associations with Alzheimer's disease diagnoses . MAPK5, a kinase associated with tangle‐related tau hyperphosphorylation, is a likely PTPRD dephosphorylation target on the basis of ptp‐3 knockout data .…”
Section: Ptprd Genomic Variation and Ptprd Associations With Human DImentioning
confidence: 52%
“…The only other oligogenic influence was that of the well‐known APOE4 / TOMM40 variants. There was nominal association with Alzheimer's pathological diagnosis in this report, though PTPRD has not previously displayed robust associations with Alzheimer's disease diagnoses . MAPK5, a kinase associated with tangle‐related tau hyperphosphorylation, is a likely PTPRD dephosphorylation target on the basis of ptp‐3 knockout data .…”
Section: Ptprd Genomic Variation and Ptprd Associations With Human DImentioning
confidence: 52%
“…The etiology of LOAD is likely to be motivated by both environmental and genetic components. However, the genetic component seems to a major determinant as the heritability of the disease has been estimated to be ∼ 80% [21]. Therefore, genetic testing hold the potential to provided sufficiently accurate predictions of the disease using genetic data exclusively.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic component of LOAD has been estimated to be 79%. However, recent studies on the heritability of LOAD have estimated that common genetic variants identified by genome-wide association studies (GWAS) are only capable to explain 33% of the phenotypic variance, meaning that over 40% of the genetic component remains unexplained [21].…”
Section: Introductionmentioning
confidence: 99%
“…The functional mechanisms of TREM2 in Aβ uptake by microglia are also complicated, and contradictory biological consequences are observed in mouse models (see e.g., (Gratuze et al, 2018) for a review on this topic). Moreover, adding up the APOE variant and other nine identified top SNPs accounts for a small portion (5%) of variation of age-of-onset (Raghavan and Tosto, 2017), suggesting that missing genetic mechanisms contribute to this complex disease. We expect that discovery of additional AD associated genetic variants will provide more insights into the understanding of the AD pathology.…”
Section: Introductionmentioning
confidence: 99%